Minimally invasive versus standard extracorporeal circulation system in minimally invasive aortic valve surgery: a propensity score-matched study. (20th November 2019) - Berretta, Paolo; Cefarelli, Mariano; Montecchiani, Luca; Alfonsi, Jacopo; Vessella, Walter; Zahedi, Mohammad Hossein; Carozza, Roberto; Munch, Christopher; Di Eusanio, Marco
Abstract: : OBJECTIVES: The impact of minimally invasive extracorporeal circulation (MiECC) systems on the clinical outcomes of patients undergoing minimally invasive aortic valve replacement (MI-AVR) has still to be defined. This study compared in-hospital and 1 year outcomes of MI-AVR interventions using MiECC systems versus conventional extracorporeal circulation (c-ECC). METHODS: Data from 288 consecutive patients undergoing primary isolated MI-AVR using MiECC ( n  = 102) or c-ECC ( n  = 186) were prospectively collected. Treatment selection bias was addressed by the use of propensity score matching (MiECC vs c-ECC). After propensity score matching, 2 groups of 93 patients each were created. RESULTS: Compared with c-ECC, MiECC was associated with a higher rate of autologous priming (82.4% vs 0%; P  < 0.001) and a greater nadir haemoglobin (9.3 vs 8.7 g/dl; P  = 0.021) level and haematocrit (27.9% vs 26.4%; P  = 0.023). Patients who had MiECC were more likely to receive ultra-fast-track management (60.8% vs 26.9%; P  < 0.001) and less likely to receive blood transfusions (32.7% vs 44%; P  = 0.04). The in-hospital mortality rate was 1.1% in the MiECC group and 0% in the c-ECC group ( P  = 0.5). Those in the MiECC group had reduced rates of bleeding requiring revision (0% vs 5.3%; P  = 0.031) and postoperative atrial fibrillation (AF) (30.1% vs 44.1%; P  = 0.034). The 1-year survival rate was 96.8% and 97.5% for MiECC and c-ECC patients, respectively ( P  = 0.4). CONCLUSIONS: MiECC systems were a safe and effective tool in patients who had MI-AVR. Compared with c-ECC, MiECC promotes ultra-fast-track management and provides better clinical outcomes as regards bleeding, blood transfusions and postoperative AF. Thus, by reducing surgical injury and promoting faster recovery, MiECC may further validate MI-AVR interventions.